Meta Analysis of the effect of acupoint sticking application for rheumatoid arthritis (穴位贴敷疗法治疗类风湿性关节炎疗效的Meta分析) - GUO Yali (郭亚丽); LI Haiting (李海婷); JIA Sansan (贾伞伞); WEN Caoli (文曹丽); ZHANG Yun (张云) (Association of Integrative Nursing, 2021)
Objective To systematically evaluate the effect of acupoint sticking application for rheumatoid arthritis, and to provide clinical evidence-based. Methods Literatures were available by searching the database including CNKI, Wanfang Data, VIP, CBM, PubMed, Embase and Cochrane library, and then two independent researchers respectively screened and determined the final inclusion literatures in the study. Using Assessing risk of bias in Cochrane Handbook evaluated the quality of literatures, and finally made a Meta analysis using Rev Man 5. 3 software. Results Acupoint sticking application combined with conventional western medicine was more efficient than conventional western medicine(OR=3. 32, 95%CI［1. 87, 5. 90］, Z=4. 10, P<0. 01); Acupoint sticking application was superior to other groups in VAS respect(SMD=-0. 42, 95%CI［-0. 66, -0. 18］, Z=3. 46, P<0. 01); Compared with conventional western medicine, acupoint sticking application with conventional western medicine can relieve the clinical symptoms of rheumatoid arthritis such as morning stiffness(MD=-11. 95, 95%CI［-17. 73, -6. 17］, Z=4. 05, P<0. 01), arthroncus(MD=-1. 75, 95%CI［-2. 07, -1. 43］, Z=10. 72, P<0. 01), joint tenderness(MD=-1. 88, 95%CI［-2. 33, -1. 43］, Z=8. 14, P<0. 01). Conclusion Acupoint sticking application can improve the clinical effect of rheumatoid arthritis, and at the same time , multi-center, large-sample, high-quality clinical studies are needed in the future. (目的 系统评价穴位贴敷疗法治疗类风湿性关节炎的疗效, 为临床提供循证依据。方法 检索中国知网、万方、维普、中国生物医学文献数据库和PubMed、Embase、Cochrane图书馆, 经2人独立筛选确定纳入研究文献, 通过Cochrane手册"偏倚风险评估"工具对文献质量评价, 采用Review Manager 5. 3软件进行meta分析。结果 穴位贴敷疗法联合常规西药治疗类风湿性关节炎比常规西药总有效率高［OR=3. 32, 95%CI(1. 87, 5. 90), Z=4. 10, P＜0. 01］; 视觉模拟评分(VAS)方面, 穴位贴敷疗法优于其他组别［SMD=-0. 42, 95%CI(-0. 66, -0. 18), Z=3. 46, P＜0. 01］; 穴位贴敷疗法联合常规西药缓解类风湿性关节炎临床症状上优于常规西药［晨僵时间: MD=-11. 95, 95%CI(-17. 73, -6. 17), Z=4. 05, P＜0. 01; 关节肿胀: MD=-1. 75, 95%CI(-2. 07, -1. 43), Z=10. 72, P＜0. 01; 关节压痛: MD=-1. 88, 95%CI(-2. 33, -1. 43), Z=8. 14, P＜0. 01］。结论 穴位贴敷疗法可以提高类风湿性关节炎临床疗效, 未来尚且需要多中心、大样本、高质量的临床研究进行佐证。)